A global bibliographic review of soil variability trends on arable land: An impetus to sustainable land management - Kuunya, Ronald; Ocwa, Akasairi; Széles, Adrienn; Ragán, Péter (Acta Agraria Debreceniensis, 2025)
Crop production is significantly affected by soil properties under the influence of climate, management practices, and geographical location. Soil variability affects the development, quality, biochemical reactions, and heterogeneity of soil. The most recent research has focused on soil variability monitoring, highlighting the importance of soil testing. This review aimed at identifying global research trends and assessing soil testing in monitoring variability on arable land, based on the bibliographic method. Literature search in Scopus Database (2020-2023) yielded 8,898 documents, refined to 815 articles. VOSviewer 1.6.20 Software was used for analysing exported data. The results revealed a growing emphasis on monitoring soil variability, with key countries including India, United States of America (USA), China, Australia, Canada, United Kingdom, and Brazil. Funding mainly came from Asia, North America, and Europe. Common monitoring approaches included soil tests and remote sensing, focusing on organic carbon, nitrogen, phosphorus, potassium, microorganisms, and soil moisture. However, digital illiteracy and high costs were major hindrances to using remote sensing and modern soil testing tools. The study suggests that whereas soil variability monitoring is essential for sustainable land management, development of affordable soil testing equipment and improved digital education are needed for its enhanced adoption.